The art of Dreamworks' "How to train your dragon, the hidden world" - Sunshine, Linda; Deblois, Dean; Baruchel, Jay 1982-; DeFaria, Christopher 1959-; Ferrera, America 1984- (Milwaukie, OR Dark Horse Books, 2019)
"In this brilliantly illustrated, full-color book, Dark Horse Books and DreamWorks Animation join forces to celebrate the climatic third film showcasing more adventures of Toothless and Hiccup. Featuring hundreds of pieces of original art and commentary from director Dean De Blois and the many talented artists and filmmakers who have created this masterpiece of storytelling and animation"--
Introduction : The story of How to train your dragon, the hidden world / Dean DeBlois --
The quest for safety : Toothless ; Light Fury ; Dragons in love ; Crimson Goregutter ; Hobgobblers --
The quest for family : The Isle of Berk ; Hiccup ; Astrid ; The dragon riders ; Fishlegs ; Snotlout ; Ruffnut & Tuffnut ; Gobber ; Valka ; Eret --
The quest for vengeance : Grimmel ; The Deathgrippers ; Grimmel's airship ; Warlords ; Trapper barge --
The quest for sanctuary : New Berk ; The caldera ; The hidden world ; The mushroom forest ; King Island --
The quest's end : The wedding ; The kids ; Night lights --
Afterword : The end is just the beginning / Chris deFaria.
Keywords: DreamWorks Animation; How to train your dragon, the hidden world (Motion picture) -- Pictorial works; Animated films -- United States; Animation (Cinematography) -- Technique; Dragons -- Pictorial works; Animated films